Pengaruh model pembelajaran kooperatif tipe think pair share (tps) terhadap kemampuan penalaran matematis siswa kelas VII MTs Bahrul Ulum - Anggraini, Ayu Kusadiah; Isharyadi, Ratri; Annajmi (Karoteh Utama, 2020)
This study aims to determine the effect of the Think Pair Share (TPS) cooperative learning model on the mathematical reasoning abilities of seventh-grade students at MTs Bahrul Ulum. This research is a quasi-experimental study with a Two-Group Posttest Only design. The population consists of all seventh-grade students at MTs Bahrul Ulum. Samples were taken using simple random sampling, resulting in class VII B as the experimental group and class VII A as the control group. The experimental class used the Think Pair Share (TPS) learning model, while the control class used conventional learning methods. Hypothesis testing was conducted using the Mann Whitney test because the normality test prerequisite showed that the data were not normally distributed. The calculation results showed Zcount>Ztabel, which is 3.85 > 1.96 with an alpha value of 0.05, leading to the rejection of H0​. Therefore, it can be concluded that the Think Pair Share (TPS) learning model has an effect on the mathematical reasoning abilities of seventh-grade students at MTs Bahrul Ulum.